Enhancing Practicality of Web-Based Mobile Learning in Operating System Course: A Developmental Study - Hakiki, Muhammad; Surjono, Herman Dwi; Wagiran; Fadli, Radinal; Budiman, Ridho Dedy Arief; Ramadhani, Witri; Habibie, Zulqoidi R.; Suhardiman, Sani; Hidayah, Yayuk (International Journal of Interactive Mobile Technologies (iJIM), 2023)
Web-based Mobile Learning can enhance the learning experience in various educational contexts. However, in operating system courses, practical challenges arise when implementing a web-based mobile learning platform, which impacts the effectiveness and accessibility of learning materials for students. To overcome these challenges, this research and development (R&D) aims to improve the practicality of web-based mobile learning in operating system courses. The research adopts a systematic 4D (Define, Design, Develop, Disseminate) model to identify and explore strategies to optimize the practicality of the platform. Data collected from lecturers and students showed a high average value of practicality, 88.33% and 88.35%, respectively. This research contributes to improving the practical aspects of web-based mobile learning, thereby enhancing students’ learning experience and outcomes in the context of operating system courses.